New Agents Targeting Angiogenesis in Glioblastoma. (2nd November 2011) - Timotheadou, Eleni
Abstract : Glioblastoma is the most common malignant glioma in adults, and despite recent advances in standard treatment, the prognosis still remains dismal, with a median survival of 15 months. The incorporation of bevacizumab in the standard treatment of relapsed glioblastoma has been a significant step towards combining targeted agents with chemotherapy, and there is an increasing number of new antiangiogenic agents in various stages of development, that are being tested both in relapsed and newly diagnosed disease, alone or in combination with standard treatment. The relatively favorable toxicity profile for most of them presents an advantage, but several concerns arise regarding their actual efficacy on the clinical level and the most efficient schedule of administration for each of them, as their molecular targets and patterns of action may vary significantly. This may lead to future modifications of the current rational of administering these agents concomitantly with initial chemotherapy or maintenance treatment.